Durasi tidur, asupan energi, dan aktivitas fisik dengan kejadian obesitas pada tenaga kesehatan puskesmas - Ramadhaniah Ramadhaniah; Madarina Julia; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: The prevalence of obesity among adults has increased globally in both developed and developing countries, including Indonesia. Obesity occurs because of imbalance of energy intake and output in the long term and it can also be seen by calculating the value of the body mass index (BMI). The main risk factors are the reduction in the duration of sleep that causes increased energy intake and reduced physical activity, in addition to other factors such as gender, income, pregnancy, smoking and alcohol, health conditions, genetics, and psychology.Objective: To determine the relationship between sleep duration, energy intake and physical activity with obesity on health centers’ workers of Pidie Jaya District in Aceh Province.Method: This study was an observational study with a cross-sectional design. The research was conducted on health workers in 11 health centers in Pidie Jaya District of Aceh Province who met inclusion and exclusion criteria. The subjects were 200 people selected using simple random sampling. Obesity was assessed by BMI (weight in kg/height in m). Duration of sleep and physical activity were collected with a form of activity recall and energy intake with a food recall. Data were analyzed by Chi-Square test and multiple logistic regression.Results: There was a relationship between sleep duration and obesity with an OR value of 2.59; there was a relationship between energy intake and obesity (OR=2.55), and there was a relationship between physical activity and obesity (OR=2.47).Conclusions: Lack of sleep duration, high energy intake and low physical activity increased the risk of obesity on health centers’ workers in Pidie Jaya District of Aceh Province.